La Dimensión Cultural en la Formación de Enseñantes de Español Para Inmigrantes - Rubio-Manriquez, M; Rubio-Martin, R (Servicio de Publicaciones. Universidad de Alcala, 2022)
The cultural dimension in the training of teachers of Spanish for inmigrants. The purpose of this work is to characterize the role of cultural dimension from the perspective of the development of inter-cultural competence, experienced by a group of university students who teach Spanish as a foreign language to adult immigrants of different nationalities in Santiago de Chile. This research is based on the qualitative analysis of this group of instructors’ teaching experiences, through the process of reflection on action and identification of critical incident to build shared pedagogical knowledge. As a result, a change in the static idea of culture is identified, one’s own culture is relativized, and an idea of culture as a dynamic element starts to emerge, which is reconfigured through dialogue in a framework of mutual recognition and empathy. © 2022. Universidad de Alcalá. All Rights Reserved.